(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2024)
This article offers a reflection on the notion of progress. A notion that received a special contribution from Immanuel Kant, who gave it the condition of purpose and objective of consciences and human history. A little later, this condition was questioned and reformulated by Charles Darwin who, from a science of life, conceived both for living organisms and for humanity a progress with no other purpose than that of their conservation and reproduction, as a result of what he called “blind variation”. Finally, this quarrel received from Georges Canguilhem care and development that resulted in a new and distinct notion of progress that has as its main content the concept of biological normativity, applicable both to living organisms and to social organizations. A concept that, in the Bachelardian manner, “denies and complements” the notion of progress of its predecessors.